Pengetahuan Remaja Putri Tentang Kesehatan Reproduksi Dengan Status Gizi Remaja - Hanik Malikhatin; Christina Pernatun Kismoyo; Masyi Wimmy Johandika (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2018)
Background: The age of adolescents is the most vulnerable age to experience reproductive health problems. BasicHealth Research Results (2013) showed in DIY the prevalence of adolescents with malnutrition status was 2.4%,underweight nutrition at 4.9%, and obesity by 4.2%. The health status of today’s adolescents will determine thepicture of the health status of the adult population in the following decade, therefore adolescent health occupies animportant position on a global scale.Objective: To find out the relationship between the knowledge of young women about reproductive health andnutritional status in SMA Negeri 1 Srandakan.Research Methods: Quantitative research, with analytic survey design, cross-sectional approach, population 148and samples taken 66 using stratified random sampling techniques, data collection tools using questionnaires, univariate analysis with frequency distribution and bivariate analysis using Kendal-tau.Results: Knowledge of young women about reproductive health with a good category (53.1%) with normal nutritional status. Knowledge of good categories (34.7%) with underweight nutritional status and good level of adolescent knowledge (12.2%) with overweight nutritional status. There is no significant relationship between the level ofknowledge of reproductive health with adolescent nutritional status p-value (0.313)> significant level (0.05).Conclusion: There is no relationship between the knowledge of young women about reproductive health and nutritional status in SMA Negeri 1 SrandakanKeyword: Adolescents, knowledge of reproductive health, nutritional status